Pemikiran Abdurrahman Wahid tentang Prinsip Pendidikan Islam Multikultural Berwawasan Keindonesiaan - Eko Setiawan (Faculty of Education and Teacher Training, Institut Agama Islam Negeri Pekalongan, 2017)
This article amis to explain Gus Dur’s concept related to multicultural Islamic education based on Indonesian concept.By using library Research method, this study provides some concept of Gus Dur. He argued that cultural diversity which has positive connotations can be realized by several aspects, one of them is education. As a figure that was usually called as the Father of Pluralism and Multiculturalism, he explained that education should be varied and based on its culture. The variety in education does not mean deviating the education goal, but it is an attempt to achieve the goal of education in varied ways. The paradigm of multicultural education includes subjects which discuss about injustice, poverty, oppression and backwardness of minority groups in the field of social, culture, Economisc, education, etc. This paradigm will encourage the growth of studies on